Leveraging artificial intelligence for enhanced electronic course design and student achievement: Unlocking the potential of AI in education - Mohammed, Mohammed Ahmed Elhossiny; Al-Osail, Abdulaziz Faleh; Assiry, Bodoor; Ibrahim, Sherif Ahmed; Abdellatif, Mohamed Sayed; Alagiri , Mohamed Taha Abd Alkhaleek; Elbagoury, Mohamed Abd Eldayim (Research Journal in Advanced Humanities, 2025)
This study explores integrating artificial intelligence (AI) tools in electronic course design, focusing on its effectiveness, challenges, and implications for educators and students. The research uses surveys, interviews, and case studies to understand the impact of AI-driven features on various aspects of the learning process. Findings show that AI tools can improve accessibility, engagement, and learning outcomes, with features like personalized learning activities and adaptive assessments catering to diverse learning needs. However, integrating AI into education faces challenges such as educators' lack of technical expertise, resistance from colleagues/administration, and ethical considerations surrounding AI algorithms. The study emphasizes the need for ongoing professional development initiatives, advocacy efforts, and clear ethical guidelines to facilitate AI's effective and responsible use in educational contexts. Collaboration between researchers, educators, and policymakers is crucial in navigating the complexities of AI integration. Fostering interdisciplinary partnerships can harness AI's full potential to create more engaging, accessible, and effective learning experiences for diverse student populations. Continuous research and innovation in AI technologies and thoughtful pedagogical approaches are essential to ensure AI integration aligns with evolving educational needs. This research contributes to a deeper understanding of AI's transformative role in education and provides valuable insights for shaping future research agendas and practices.